ANALYSIS OF RISKS AND CONSEQUENCES IN A SUGAR-ALCOHOL PLANT - Martisthela Passoni de Araújo Marin; Gabriela Messias de Melo; Guilherme Barbosa Henke de Paulo; Luiz Fernando Machado Labate; Thiago Baco Miranda; Vanessa Schincariol (The Journal of Engineering and Exact Sciences, 2017)
The existing risks of the sugar-alcohol industry were analyzed by dividing the process into blocks and identifying the main risks, as well as the removal of dangerous substances from the process, mainly anhydrous alcohol, hydrated alcohol and sugar, due to the large volume in the process and its physical- Chemical properties. It was verified that 90% of the accidents involving ethanol occur in road transport and 2% in industry and storage. Risk analysis was carried out in product storage and transportation. PHAs, ETA and Hazops were applied as qualitative methods of analysis. The Phast ® software showed that the largest range was 169.9 meters in the release of Ethanol by rupturing the 10,000 m³ reservoir. The social and individual risks were also obtained. The results indicate that fatalities will occur only within the industry, just indicating individual risk. This risk reaches a maximum of 1E-04, considered intolerable by CETESB.